Emerging translational research on magnetic nanoparticles for regenerative medicine. (12th June 2015) - Gao, Yu; Lim, Jing; Teoh, Swee-Hin; Xu, Chenjie
Abstract : This review summarizes current advances, challenges, and future opportunities of magnetic nanoparticles for regenerative medicine. Abstract : Regenerative medicine, which replaces or regenerates human cells, tissues or organs, to restore or establish normal function, is one of the fastest-evolving interdisciplinary fields in healthcare. Over 200 regenerative medicine products, including cell-based therapies, tissue-engineered biomaterials, scaffolds and implantable devices, have been used in clinical development for diseases such as diabetes and inflammatory and immune diseases. To facilitate the translation of regenerative medicine from research to clinic, nanotechnology, especially magnetic nanoparticles have attracted extensive attention due to their unique optical, electrical, and magnetic properties and specific dimensions. In this review paper, we intend to summarize current advances, challenges, and future opportunities of magnetic nanoparticles for regenerative medicine.